2010
DOI: 10.1007/s10067-010-1372-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum hyaluronic acid levels do not explain morning stiffness in patients with fibromyalgia

Abstract: To investigate the serum levels of hyaluronic acid (HA) in Korean female patients with fibromyalgia (FM) and correlate these levels with variables of disease severity including morning stiffness, we measured HA serum levels in 69 FM patients, 72 rheumatoid arthritis (RA) patients, and 71 healthy controls by enzyme-linked binding protein assay. The serum levels of HA in FM patients did not differ from those in the age-matched controls, whereas HA levels were significantly higher in RA patients than in FM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In serum, 8 studies reported significantly higher levels of IL-6 among patients with FM compared with HC 14,31,41,53,58,82,86,93 and 7 studies reported significantly higher levels of IL-8 in patients with FM as well. 15,14,44,58,83,88,93 Five studies reported higher levels of CRP in serum in patients with FM, 4,15,33,64,93 whereas 3 studies found no differences. 2,67,78 Five studies reported higher levels of BDNF in FM, 22,32,51,63,75 8 studies assessed TNF-α and reported higher levels in patients with FM, 15,14,17,22,31,81,86,88 and 1 study reported higher levels of IL-10 in FM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In serum, 8 studies reported significantly higher levels of IL-6 among patients with FM compared with HC 14,31,41,53,58,82,86,93 and 7 studies reported significantly higher levels of IL-8 in patients with FM as well. 15,14,44,58,83,88,93 Five studies reported higher levels of CRP in serum in patients with FM, 4,15,33,64,93 whereas 3 studies found no differences. 2,67,78 Five studies reported higher levels of BDNF in FM, 22,32,51,63,75 8 studies assessed TNF-α and reported higher levels in patients with FM, 15,14,17,22,31,81,86,88 and 1 study reported higher levels of IL-10 in FM.…”
Section: Resultsmentioning
confidence: 99%
“…22,32,37,51,63,71,75 Eight studies (26%) assessed CRP in serum and one study in whole blood. 1,2,4,15,27,33,67,78,93 Six studies assessed IGH and GH, 3 in serum, and 3 in whole blood, 23,27,57,66,73,78 and 19 (45%) studies assessed different anti-inflammatory and proinflammatory immune mediators in serum, for example (IL-1 and 1B, IL-6, IL-4, IL-8, IL-10, TNF-a, and IFN-g. 3,15,14,22,31,37,41,44,54,58,61,63,71,72,82,83,86,88,93 Further details for the investigated blood biomarkers were shown in Table 2.…”
Section: Investigated Blood Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased levels of pro-inflammatory cytokines, such as TNF-α, IL-1β and IL-6 and their mediators, were detected in the suffering animals compared to the controls, confirming the key role of inflammation in fibromyalgia [ 90 , 91 ]. Among these circulating biomarkers, calcitonin gene-related peptide (CGRP) is also dysregulated and may be a reliable parameter to help diagnose this complex syndrome [ 92 ], while there were no differences in vascular endothelial growth factor (VEGF) and nitric oxide (NO) levels between patients and controls [ 93 ]. The IL-6-R-Ab administration reduced proinflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 99%